Rekomendasi Pengelolaan Hara Terpadu Berdasarkan Interpretasi Hasil Analisis Tanah Pertanian Di Kabupaten Garut - Asfianti, Asti; Fajarfika, Resti; Sativa , Novriza (JAGROS : Jurnal Agroteknologi dan Sains (Journal of Agrotechnology Science), 2025)
Agriculture in Garut Regency, as a center for food and horticultural production, faces challenges due to declining soil fertility resulting from fertilizer practices that are not yet fully based on site-specific conditions. This study aims to interpret soil analysis results to determine soil fertility status and develop site-specific integrated nutrient management recommendations to improve fertilizer efficiency and ensure the sustainability of agricultural systems. The research was conducted on agricultural land in Sukamaju Village (Cilawu Subdistrict) and Cikandang Village (Cikajang Subdistrict), Garut Regency. Soil samples were purposively collected from a depth of 0–30 cm during October 2025. Soil analyses included pH, organic carbon, P HCl 25%, K HCl 25%, CEC, and base saturation to support site-specific fertility assessment and nutrient management planning. Soil chemical analysis in Sukamaju Village (Cilawu Subdistrict) showed a pH of 8,2 and organic carbon content of 4.73%. The P₂O₅ HCl 25% value was recorded at 91,20 mg.100 g-1, K₂O HCl 25% at 52,15 mg.100 g-1, CEC at 41,30 cmol.kg-1, and base saturation at 63,12%, indicating a high soil fertility status. Meanwhile, soil analysis in Cikandang Village (Cikajang Subdistrict) revealed a pH of 7, soil organic carbon of 5,58%, P₂O₅ HCl 25% of 99,53 mg.100 g-1, K₂O HCl 25% of 52,15 mg.100 g-1, CEC of 47,85 cmol.kg-1, and base saturation of 25,16%, indicating a low fertility status. Fertility maintenance strategies are recommended for high status soils, while nutrient balance improvement particularly for base cations and potassium is advised for low fertility soils.